Farmers’ Strategic of the Sustainability of Corporate-Based Cassava Farming: A Study of Technology Adoption on Farming Performance - Muttaqien Zuhri Nur; Khamdi Ali; Imam Santoso Wahyu; Maulida Suci Ayomi Nun; Puspita Nurul; Suharti Suharti; Purwanto Edy; Linu Ibrahim Agusnawan; Dimitha Nurulia; Danil Furqansyah M. (E3S Web of Conferences)
Technology adoption is crucial for agribusiness growth, enabling farmers to meet competitive market demands. Rural farmers need to adopt technology to improve their businesses and lives. This study aims to identify the most prominent factors that influence the adoption of corporate-based cassava farmer technology on farming performance. Using a quantitative method, the study was conducted in Puntukrejo Village, Karanganyar Regency, Indonesia. In this study, which included 65 respondents, structural equation modelling (SEM-PLS) based on WARP-PLS was used to identify the critical features that yield the best agricultural performance. The results showed that creativity, annual income, education, and land suitability affect technology adoption. The creativity variable had the most significant path coefficient, indicating that farmers’ success will be significantly influenced by their level of creativity. The study suggests that enhancing land suitability, annual income, and education could significantly encourage the community to embrace technology for sustainable cassava farming.